2022
DOI: 10.1039/d2ea00031h
|View full text |Cite
|
Sign up to set email alerts
|

Secondary aerosol formation during the dark oxidation of residential biomass burning emissions

Abstract: Particulate matter from biomass burning emissions affects air quality, ecosystems and climate; however, quantifying these effects requires that the connection between primary emissions and secondary aerosol production is firmly established....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 91 publications
2
13
0
Order By: Relevance
“…2), suggesting the importance of aqueous nitrate radical reactions for oxidizing bbOA. The latter has also been observed by Kodros et al (2020) and Kodros et al (2022).…”
Section: General Description Of Primary Biomass Burning Organic Aeros...supporting
confidence: 66%
“…2), suggesting the importance of aqueous nitrate radical reactions for oxidizing bbOA. The latter has also been observed by Kodros et al (2020) and Kodros et al (2022).…”
Section: General Description Of Primary Biomass Burning Organic Aeros...supporting
confidence: 66%
“…NO 2 in the presence of O 3 is partially converted into ˙NO 3 , which is the main oxidant during nighttime 52 and important in ageing of optically dense biomass burning plumes during daytime. 53 The dark ageing conditions of the flaming biomass burning aerosol resemble the experimental conditions of Kodros et al (2022), 54 but at higher biomass burning aerosol concentrations. Assuming that the majority of O 3 reacts with NO 2 , substantial generation of ˙NO 3 may be expected, particularly for the biomass burning aerosol generated under flaming conditions.…”
Section: Methodsmentioning
confidence: 59%
“…presence of O 3 is partially converted into cNO 3 , which is the main oxidant during nighttime 52 and important in ageing of optically dense biomass burning plumes during daytime. 53 The dark ageing conditions of the aming biomass burning aerosol resemble the experimental conditions of Kodros et al (2022), 54 but at higher biomass burning aerosol concentrations.…”
Section: Photo-lac Characterisationmentioning
confidence: 68%
“…9 displays the evolution of pellet bbOA during nighttime and daytime aging in our experiments. During the daytime the OA changes chemically and aer 4 h it approaches in this space the aged under dry conditions bbOA spectrum of Kodros et al 62 and also some of the OOA factors found in winter periods. For dark aging the role of RH is evident.…”
Section: Nighttime Soa Formation: Wood Vs Pelletsmentioning
confidence: 84%
“…This is a good assumption, given that the biomass burning aerosol pH is expected to be high enough so that most of the nitrate and chloride are in the aerosol phase. 62,67 The potassium concentration was scaled as 15% of the PM nitrate. 68 The concentrations of non-volatile cations such as sodium, calcium, and magnesium were assumed to be zero as their contribution to the sub-micrometer mode is considered to be negligible.…”
Section: Data Analysis and Methodsmentioning
confidence: 99%